Copper(II) Inhibition of the SARS‐CoV‐2 Main Protease - Roberto A. Garza‐López; Liam Kwak; Andrew Chung; Gabriel L. Ancajas; John J. Kozak; Harry B. Gray (Natural Sciences)
ABSTRACT In an analysis of the structural stability of the coronavirus main protease (Mpro), we identified regions of the protein that could be disabled by cobalt(III)‐cation binding to histidines and cysteines. Here we have extended our work to include copper(II) chelates, which we have docked to HIS 41 and CYS 145 in the Mpro active‐site region. We have found stable docked structures where Cu(II) could readily bond to the CYS 145 thiolate, which would be lethal to the enzyme. We investigated the structural basis of Cu(II) Schiff‐base chelates as potential Mpro inhibitors in silico. Using induced‐fit docking (IFD) and molecular dynamics (MD) simulations, we identified the binding mode and assessed the stability of Mpro inhibition. Our results show that Cu(II) chelates form stable complexes with HIS 41 and CYS 145, with Cu(II) bonding to the CYS 145 thiolate. This irreversible binding is anticipated to effectively inhibit Mpro activity, thereby preventing the proteolytic processing of the SARS‐CoV‐2 polyprotein into functional proteins necessary for viral activity. Our findings suggest that Cu(II) Schiff‐base chelates are promising candidates for the irreversible inhibition of SARS‐CoV‐2 Mpro.